Peningkatan Kemampuan Motorik Kasar melalui Permainan Lempar Bola pada Anak Usia 4-5 Tahun - Titi Haryanti; Nahdiyah Hidayah (ANWARUL, 2026)
Although the gross motor development of young children has been widely studied, research that specifically examines the application of ball-throwing games as a structured instructional strategy for 4–5-year-old children remains limited. This study aimed to improve the gross motor skills of children aged 4–5 years through ball-throwing games at KB Mambaul Ma’arif Belik. A qualitative approach was employed using a Classroom Action Research (PTK) design based on the Kemmis and McTaggart model, implemented in two cycles with 25 children in Group A as the research subjects. Data were collected through observation, documentation, and gross motor skill assessment sheets, then analyzed using qualitative descriptive techniques and percentages to identify changes in children’s gross motor development achievements. The findings show a significant improvement in children’s gross motor skills, with the average achievement increasing from 50.00% at baseline to 88.80% in the second cycle. The implementation of ball-throwing games proved effective in enhancing children’s strength, coordination, and movement accuracy. The study concludes that ball-throwing games constitute an effective and enjoyable alternative for gross motor learning in early childhood education institutions and recommends their systematic integration into learning activity planning to support the optimal development of gross motor skills in young children.